2011
DOI: 10.1097/iae.0b013e31820a67cc
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentations of Multiple Evanescent White Dot Syndrome Without White Dots

Abstract: Our case series demonstrates another atypical presentation of multiple evanescent white dot syndrome that has not been described previously: foveal involvement at the onset of the disease without white spots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
0
18
0
2
Order By: Relevance
“…The number of white spots is very variable, and in fact they may be absent. 32 Some investigators have suggested that MEWDS is a choroidal vascular disease. Others have considered it to be a disease of the RPE or outer retina.…”
Section: Discussionmentioning
confidence: 99%
“…The number of white spots is very variable, and in fact they may be absent. 32 Some investigators have suggested that MEWDS is a choroidal vascular disease. Others have considered it to be a disease of the RPE or outer retina.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic FA findings in MEWDS might contribute to its diagnosis, although some atypical FA aspects, such as foveal granularity without the typical white dots and associated vasculitis, were found in this study (Figures 2 and 3) (6,7) . Besides FA, other complementary exams can reveal MEWDS-like lesions, including indocyanine green angiography and autofluorescence exams showing hypocyanescent and hypo-autofluorescent lesions, respectively, which correspond to the white dots and other lesions not detected during ophthalmoscopic examination (8)(9)(10)(11) .…”
Section: Discussionmentioning
confidence: 81%
“…[4][5][6][7][8][9][10][11] Olguların yaklaşık olarak %50'sinde vitreusta hücre olabileceği ancak ön kamarada hücrenin genellikle olmadığı bilinmektedir. 3 Bu olguda ise önce ön kamara hücrelerinin hemen sonrasında da vitreus hücre-leri ve tipik retina lezyonlarının ortaya çıktığı atipik başlangıçlı bir multipl geçici beyaz nokta sendromu olgusu sunulmaktadır.…”
Section: Discussionunclassified
“…Literatürde ileri yaş başlangıçlı, bilateral, tekrarlayıcı, koroid neovasküler membran oluşu-muna neden olan, multifokal koroidit veya akut idiyopatik kör nokta genişlemesi sendromu ile birlikte ortaya çıkan ve karakteristik beyaz noktaların görülmediği atipik olgular sunulmuştur. [4][5][6][7][8][9][10] Çalışmamızda, prodromal dönemde ön üveit tanısı konulup takibinde multipl geçici beyaz nokta sendromu bulguları ortaya çıkan atipik başlangıçlı bir olgu sunulmuştur.…”
unclassified